Peran citra merek hijau, niat merek untuk meningkatkan loyalitas pembelian - Rahayu, Sri; Nanik, Rin; Sulastri, Susi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2021)
This study aims to determine the role of green brand image in an effort to increase brand intention, and purchase loyalty. Research locations were held in various universities in the province of D.I.Yogyakarta. The population of this research is university students, and the research sample is 222 students. The sampling technique uses purposive sampling technique, minimum age 18, and a maximum 25 years old, laptop users at least 1 year. Data were collected through a survey by distributing questionnaires. The research data is processed using structural equation modeling, AMOS 21 program. The results of this study indicate that green brand image has a positive and significant effect on brand intention, and purchase loyalty. The more the green brand image increases, the more brand intention and purchase loyalty increases. This study also has limitations, and includes suggestions for future research.